Configurações e relações estabelecidas no estágio curricular supervisionado na formação inicial de professores de educação física - Silva Júnior, Arestides Pereira da (2016)
The purpose of this research was to analyze, in the light of Norbert Elias's theory, how the configurations and relationships established in the Supervised Curricular Internship (SCI) in the initial formation of Physical Education (PE) teachers have an impact on the autonomy of Performance and in the pedagogical practice of the academics in training. The context of the research involved the PE course - graduation, from the Universidade Estadual de Maringá (UEM). The research was structured and presented in the "Scandinavian Model", composed of five articles. The first, a systematic review, aimed to analyze in the national periodicals the production of the knowledge about the SCI in the formation of PE teachers, from a systematic review. It was verified that there was an increase in the production of knowledge on this subject in the last years, especially from the year 2010. In the second article, the objectives were to present and discuss the main laws that sustain and subsidize SCI in the training of teachers of PE in Brazil. Significant advances were made in favor of the organization and structuring of SCI in the training of future PE teachers. The third article, characterized as a critical and exploratory essay, aimed to present and discuss the possibilities of SCI in the initial formation of PE teachers and their approximations with Norbert Elias´s theory of relations between established-outsiders. It was observed that the school is seen as a complex web of interdependent relations and power, emphasizing that the SCI in the initial formation of PE teachers should be constituted as a space of closer relations. In the fourth article, we tried to analyze the existing configurations and the relationships established between the PE trainees and the school agents in the development of the SCI, as well as this action from the different levels of education of Basic Education. The participation of 90 undergraduates from the UEM PE course and 63 PE teachers from Basic Education came from a response to a questionnaire, from which interrelations and interdependencies between the characterization of the participants, the aspects evaluated , The relationships established and the configuration of SCI at the levels of education. The purpose of the fifth article was to investigate how SCI configurations are presented and how the relationships between PE trainees (outsiders) and established school agents are established, as well as to identify the impacts on the development of the traineeship. The focus groups included 61 people linked to the implementation of the SCI, of which 33 were undergraduate students of the UEM course and 23 were teachers of Basic Education. Five SCI class coordinating teachers were also interviewed. It is concluded that the configuration of SCI presented has strengthened the distance border between trainees and school agents. As a general conclusion, based on the evidence found in the five surveys, in order to confirm the elaborated thesis, it was verified that the configurations and the relations established in the context of the SCI in the initial formation of PE teachers, either in the university or in the school, Influence the performance of the students during the internship.